Spanish for the sciences: A communication-based approach - Oscar A. Pérez (Ibérica, 2018)
This paper describes the design and implementation of an advanced Spanish for the sciences course at the college level in the United States. The course is centered on public dissemination and scholarly communication, as opposed to the predominant approach of focusing on scientific content areas. The main idea was to follow a Languages Across the Curriculum (LAC) model that shifts the responsibility of providing the scientific content of the course from the instructor to the students, allowing them to: 1) develop technical and scientific communication skills and materials, 2) explore the interrelated notions of science and culture in Spanish-speaking societies, 3) draw connections between their knowledge of both Spanish language and the sciences, 4) compare what “science” means to them to the ways this concept is perceived around the Spanish-speaking world, and 5) participate in Spanish-speaking scientific communities.